Corporate Social Responsibility 2.0: Towards a socio-transformative paradigm for business - Van der Waldt, Gerrit; Rooi, Niel; Botha, Doret (Journal of Economic Development, Environment and People, 2023)
The South African business fraternity is expected to contribute to and foster the government’s social transformation agenda. This contribution should be directed by businesses’ corporate social responsibility (CSR) intentions and organizational arrangements. However, companies’ efforts in this regard are being increasingly criticized due to the absence of a socio-transformative agenda. In other words, CSR praxis is perceived to be inadequately positioned in businesses to act as a core strategic function aimed at benefiting society. The purpose of this article is to outline the perceived failures of conventional CSR praxis and to propose a framework for businesses to adopt a socio-transformative CSR paradigm. A generic qualitative research design, utilizing document analysis and a literature survey, was followed in this study. The findings indicate that businesses do indeed need to adopt a socio-transformative business model to comply with national and international driving forces for change. Recommendations are proposed to guide businesses towards such a transformative management approach utilizing the principles of McKinsey 7-S model for business readiness and Kotter’s 8-step change management model. The study encourages corporations and firms to adopt a socio-transformative paradigm by utilizing established business readiness and change management models.